Estudio de usabilidad y accesibilidad del sitio web de la Universidad Técnica Estatal de Quevedo, cantón Quevedo, provincia de Los Ríos, año 2015. - Zambrano Bastidas, Frank Jackson (2015)
The present investigation have a great importance the study of the usability y accesibility of website of the State Technical University to Quevedo, Cantón Quevedo Province of Los Rios, age 2015 determines the factors indispensable during the process or desing of a website with the purpose that can perceive, understand, navigate and interact. In the diagnostic of the problems various factors that affect the usability and accessibility of the website, as excess links, reduced information, visual noise This led to the formulation of the problem is ¿How to detect the shortcomings identified and usability accessibility of the website of the State Technical University of Quevedo?, This led to proposing the main objective of the study evaluating the usability and accessibility of the website of the University. The methodology was aimed at addressing the types of research: From field, literature, in which the survey techniques used, and the signing where theoretical methods applied: Inductive - Deductive, Analytical; and statistical: Observation and others whose support is the information obtained through primary and secondary supported by methods and tools of research sources. In base the results obtained the 48% of the students established that the estructure of navegation actual generates drawbacks in the interaction with the user, well as analysis Realized with the tools examinator reflecting the calification of 2.5 in the scale of 1 a 10, essential considering a proposal to redesign the website of the State Technical University to Quevedo in order that it can provide accessibility and usability, it is also a necessary tool to provide information to students of the University.....